2021
DOI: 10.1002/anie.202111749
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Synthesis of Solution‐Processable Crystalline Poly(Triazine Imide) with Minimized Defects for OLED Application

Abstract: Poly(triazine imide) (PTI) is a highly crystalline semiconductor, and though no techniques exist that enable synthesis of macroscopic monolayers of PTI, it is possible to study it in thin layer device applications that are compatible with its polycrystalline, nanoscale morphology. We find that the by‐product of conventional PTI synthesis is a C−C carbon‐rich phase that is detrimental for charge transport and photoluminescence. An optimized synthetic protocol yields a PTI material with an increased quantum yiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 53 publications
(107 reference statements)
4
24
0
Order By: Relevance
“…Previous studies have shown that the absorption edge of HPHI is located on the short wavelength side compared to that of KPHI, and the results here are qualitatively consistent with this. It has recently been reported that the absorption edge is blue-shifted in PTI when the metal ion is replaced by H + , which is consistent with the trend observed for HPHI …”
Section: Results and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous studies have shown that the absorption edge of HPHI is located on the short wavelength side compared to that of KPHI, and the results here are qualitatively consistent with this. It has recently been reported that the absorption edge is blue-shifted in PTI when the metal ion is replaced by H + , which is consistent with the trend observed for HPHI …”
Section: Results and Discussionsupporting
confidence: 87%
“…For example, transition-metal dichalcogenides , and covalent organic frameworks, in addition to graphene derivatives, have been considered promising candidates. The potential of several CN polymers for optoelectronic functional materials has hardly been explored, partly because of the difficulty in preparing highly crystalline samples. , Poly­(triazine imide) (PTI), which has a structure similar to that of PHI with triazine as the building unit, has been acknowledged as a potential electroluminescent material, but it is still not being actively studied. The situation is similar for MPHI.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical modifications enhanced the values of log P and p K b in the molecules, which satisfied the criteria for mitochondria accumulation and avoided the lysosomal uptake effects . The log P of Cy1321 is determined to be 16.5 (Figure b), and the p K b is calculated to be 13.6 based on fluorescence titration assay (Figure c) . The bis-cholesterol architecture is anticipated to be anchored on the inner membrane of the mitochondria.…”
Section: Resultsmentioning
confidence: 96%
“…37 The log P of Cy1321 is determined to be 16.5 (Figure 1b), and the pK b is calculated to be 13.6 based on fluorescence titration assay (Figure 1c). 38 The bis-cholesterol architecture is anticipated to be anchored on the inner membrane of the mitochondria. Owing to its advantages of ultrasensitivity toward polarity, Cy1321 is presumed to perceive the polarity variations in the metabolic and even the PCD process within the mitochondria.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The device structure of MNCs based on electroluminescent LEDs is similar to that of traditional OLEDs, which is a typical carrier injection electroluminescent device with a “sandwich” structure, and MNCs’ thin film is used as the light-emitting layer [ 69 , 70 , 71 , 72 ]. As shown in Figure 6 , electroluminescent LEDs are generally composed of a hole transport layer (HTL), a light-emitting layer, an electron transport layer (ETL), and electrodes, and corresponding interface modifications can be performed between the layers according to special requirements.…”
Section: Electroluminescent Light-emitting Diodes With Metal Nanoclus...mentioning
confidence: 99%